More severe phenotype of early‐onset osteoporosis associated with recessive form of LRP5 and combination with DKK1 or WNT3A - Caetano da Silva, Caroline (John Wiley and Sons Inc., 2021)

(untitled) (Mol Genet Genomic Med)
BACKGROUND: Early‐onset osteoporosis (EOOP) is defined by low bone mineral density (BMD), which increases the risk of fracture. Although the prevalence of osteoporosis at a young age is unknown, low BMD is highly linked to genetic background. Heterozygous pathogenic variants in low‐density lipoprotein receptor‐related protein 5 (LRP5) are associated with EOOP. This study aimed to investigate the genetic profile in patients with EOOP to better understand the variation in phenotype severity by using a targeted gene sequencing panel associated with bone fragility. METHOD AND RESULTS: We used a sequencing panel with 17 genes reported to be related to bone fragility for analysis of 68 patients with EOOP. We found a high positivity rate of EOOP with LRP5 variants (14 patients, 20.6%). The remaining 79.4% of patients with EOOP but without LRP5 variants showed variable disease severity, as observed in patients with at least one variant in this gene. One patient, with multiple fractures and spine L1‐L4 BMD Z‐score −2.9, carried a novel pathogenic homozygous variant, c.2918T>C, p.(Leu973Pro), without any pseudoglioma. In addition to carrying the LRP5 variant, 2 other patients carried a heterozygous variant in Wnt signaling pathway genes: dickkopf WNT signaling pathway inhibitor 1 (DKK1) [NM_012242.4: c.359G>T, p.(Arg120Leu)] and Wnt family member 3A (WNT3A) [NM_033131.3: c.377G>A, p. (Arg126His)]. As compared with single‐variant LRP5 carriers, double‐variant carriers had a significantly lower BMD Z‐score (−4.1 ± 0.8) and higher mean number of fractures (6.0 ± 2.8 vs. 2.2 ± 1.9). Analysis of the family segregation suggests the inheritance of BMD trait. CONCLUSION: Severe forms of EOOP may occur with carriage of 2 pathogenic variants in genes encoding regulators of the Wnt signaling pathway. Two‐variant carriers of Wnt pathway genes had severe EOOP. Moreover, DKK1 and WNT3A genes should be included in next‐generation sequence analyses of bone fragility.